DETECTION OF FLUOROQUINOLONE RESISTANCE IN MYCOBACTERIUM TUBERCULOSIS ISOLATE CAUSED BY MUTATION IN THE GYRA GENE - Citra Wulandari; Ziske Maritska (Fakultas Kedokteran Universitas Sriwijaya, 2022)
Drug-resistant tuberculosis is a public health concern. TB that is drug-resistant to rifampin and isoniazid is known as MDR-TB, whereas XDR-TB is MDR-TB that is also resistant to second-line medicines, such as fluoroquinolones (levofloxacin, ofloxacin, and moxifloxacin). rifampin-resistant tuberculosis (RR-TB), of which 78 percent had multidrug-resistant tuberculosis (MDR-TB) (MDR-TB). Fluoroquinolones are a class of broad-spectrum antimicrobials that have become increasingly popular in recent years. Fluoroquinolones have activity against Mycobacterium tuberculosis both in vitro and in vivo. Fluoroquinolones might cause resistance if they are used inappropriately or excessively. According to several investigations, the majority of fluoroquinolone-resistant M. tuberculosis isolates (approximately 50-90 percent) had mutations in the gyrA gene QRDR Quinolone Resistance Determination Region. However, the genetic involvement of various gyrA gene mutations in resistant Mycobacterium TB isolates against fluoroquinolone resistance remains an unknown gyrA gene mutation pattern in resistant Mycobacterium tuberculosis isolates. In the previous investigation, mutations in the gyrA gene were discovered at codons 90 and 94.